Cemento-Ossifying Fibroma Presenting as a Mass of the Parapharyngeal and Masticator Space - Jung, So Lyung; Choi, Kyu Ho; Park, Young Ha; Song, Hyun Chul; Kwon, Mi Seon (American Journal of Neuroradiology, 1999)
Summary: We report a case of cemento-ossifying fibroma that presented as a large extraosseous mass in the masticator and parapharyngeal space. CT scanning and MR imaging showed a large extraosseous mass with central conglomerated, well-matured ossified nodules and fatty marrow. The central matured ossified nodules were of low density on CT scans and high signal intensity on T1- and T2-weighted MR images. Multiplanar reformatted CT scans revealed the origin of the mass to be at the extraction site of the right lower second molar tooth.